The awareness of chronic kidney disease in non-medical female university students: A cross-sectional in Riyadh, Saudi Arabia - Amen Bawazir; Maria Fayoumi; Alaa Alharbi; Arwa Alakeel; Bashayer Alskait; Areej Alsanawi; Manar Alahmari; Hala Alamer; Kholoud Alsaygh; Thekra Khattar; Njood Aleid; Mohammad Fareed (PLoS ONE, 2025)
Background Assessing the level of knowledge about Chronic Kidney Disease (CKD) is very crucial for society. Research on CKD knowledge can help to identify gaps in public understanding and develop targeted educational interventions to improve public awareness of CKD. Aim To assess the level of awareness of CKD among non-medical students in Riyadh region of Saudi Arabia. Methods A cross-sectional study was conducted between February 2023 to November 2023 including 523 non-medical female university students in Riyadh region. A self-administer questionnaire was designed and used for collecting the required data. The information viz. age, nationality, residential area, university, educational level, study field, academic year, and income were obtained from each participant. Information for knowledge of CKD knowledge and associated risk factors were also obtained in the study. Results The study concluded non-medical female university students had an unsatisfactory level of knowledge regarding CKD. We found a significant association (p < 0.05) between the adequacy of general knowledge, knowledge of risk factors, complications, and active preventive measures regarding CKD with the sociodemographic characteristics of the participants. Conclusion The study found that most non-medical female students have an unsatisfactory level of knowledge regarding CKD, therefore, educational materials should be developed and distributed to inform people more about CKD risk factors, symptoms, and treatment options like organizations that can offer educational events and webinars on CKD. These events can be a great way to learn about CKD from experts in the field and to ask questions about specific concerns.